PELIMPAHAN PORSI CALON HAJI YANG TELAH WAFAT KEPADA SALAH SATU AHLI WARIS MENURUT PERSPEKTIF HUKUM WARIS ISLAM - moulia, nouvan; Muharrir, Muharrir; Fazzan, Fazzan (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
The performance of the Hajj pilgrimage is one of the pillars of Islam that must be fulfilled by Muslims who possess the ability (istita'ah). Due to the overwhelming number of applicants and the restrictions on the number of pilgrims allowed to depart each year imposed by the Saudi Arabian government, the Ministry of Religious Affairs of the Republic of Indonesia has limited the departure of prospective Hajj pilgrims through a quota system and the allocation of waiting numbers known as